2017
DOI: 10.18632/oncotarget.16308
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 promotes breast cancer metastasis by downregulating miR-196a-3p expression

Abstract: Transforming growth factor-β1 is considered a key contributor to the progression of breast cancer. MicroRNAs are important factors in the development and progression of many malignancies. In the present study, upon studies of breast cancer cell lines and tissues, we showed that microRNA -196a-3p is decreased by transforming growth factor-β1 in breast cancer cells and associated with breast cancer progression. We identified neuropilin-2 as a target gene of microRNA -196a-3p and showed that it is regulated by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
1
26
0
2
Order By: Relevance
“…S7BC), indicating dependence on a NRP2-driven signaling cascade, to be elucidated. On a different note, it was recently shown that mesenchymal-type MDAMB231 cells are characterized by low levels of miRNA-196a-3p, which hinders both NRP2 expression and TGFb-R signaling in other breast cancer cells (31). This is consistent with the reported association between NRP2 and TGFb-R (18), as well as with the known dependence of MDAMB231 cells on the latter signaling pathway (32).…”
Section: Discussionsupporting
confidence: 85%
“…S7BC), indicating dependence on a NRP2-driven signaling cascade, to be elucidated. On a different note, it was recently shown that mesenchymal-type MDAMB231 cells are characterized by low levels of miRNA-196a-3p, which hinders both NRP2 expression and TGFb-R signaling in other breast cancer cells (31). This is consistent with the reported association between NRP2 and TGFb-R (18), as well as with the known dependence of MDAMB231 cells on the latter signaling pathway (32).…”
Section: Discussionsupporting
confidence: 85%
“…One of these intriguing cells expressing the NRP2 receptor is the microglia which is increased in the Sema 3F interneuron deletion mutant (Fig. 8a) and may play a role in neuroinflammation [64, 93, 94]. Sema 3F–NRP2 signaling has a putative role in T cell migration and blood vessel permeability into the brain [64, 95].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that miR-196a expression levels were higher in the ER+ BC tissues compared to ER- tissues, which was consistent with the results from GSE22220 dataset showing the noteworthy correlation between miR-196a levels and ER status in BC. Some reports have shown that miR-196a participates in the development of BC and acts as an oncogene [ 18 , 34 , 43 ]. Similarly, we demonstrated that interference of miR-196a attenuated estrogen-induced cell proliferation, migration and invasion in ER+ BC cells, demonstrating an important role of miR-196a in estrogen-promoted BC development.…”
Section: Discussionmentioning
confidence: 99%